Human rights and health: challenges for training nurses in South Africa - L London (AOSIS, 2008)
The need for health professionals to address their human rights obligations has emerged in the last decade both internationally as well as nationally following the findings of South Africa's Truth and Reconciliation Commission. Support for human rights norms has become a priority for institutions as well as practitioners within the health sector. Training plays a crucial role in shaping health professional practice. In addition to creating a clear understanding of the linkages between human rights and health, educators can role-model how health professionals should act to support human rights. This article explores human rights derived from the South African Constitution in relation to the obligation on health professionals to respect, protect, promote and fulfill human rights. The implications of this commitment to human rights training of nurses are discussed, drawing on the authors' nine years of experience in running courses for South African health professional educators. Themes include: developing core competencies for human rights in health professional curricula, identifying appropriate instructional methodologies and assessment tools suited to the content and context of human rights, and engaging the institutional environment for human rights teaching, at both the level of institutional culture and strategic implementation. At a time when there are increasing demands on the nursing profession to assume greater responsibility and develop versatility in its scope of practice, key challenges are posed for teaching and realising human rights.